Oral Health and Liver Disease: Bidirectional Associations-A Narrative Review - Fredrik Åberg; Jaana Helenius-Hietala (MDPI AG, 2022)
Several links between chronic liver disease and oral health have been described and are discussed in this narrative review. Oral manifestations such as lichen planus, ulcers, xerostomia, erosion and tongue abnormalities seem to be particularly prevalent among patients with chronic liver disease. These may be causal, coincidental, secondary to therapeutic interventions, or attributable to other factors commonly observed in liver disease patients. In addition, findings from both experimental and epidemiological studies suggest that periodontitis can induce liver injury and contribute to the progression of chronic liver disease through periodontitis-induced systemic inflammation, endotoxemia, and gut dysbiosis with increased intestinal translocation. This has brought forward the hypothesis of an oral-gut-liver axis. Preliminary clinical intervention studies indicate that local periodontal treatments may lead to beneficial liver effects, but more human studies are needed to clarify if treatment of periodontitis truly can halt or reverse progression of liver disease and improve liver-related outcomes.